The Theoretical Basis and Literature Review of Esg and Enterprise Performance - Fan, Dong (Asia Pacific Economic and Management Review, 2025)
This paper focuses on the relationship between ESG (Environment, Social Responsibility, and Corporate Governance) and corporate performance, with a specific emphasis on new energy enterprises. It first defines core concepts—clarifying ESG as an investment and operational philosophy guiding enterprises to balance financial and non-financial goals, and corporate performance as a measure of operational quality covering both financial and non-financial dimensions—then elaborates on two key theoretical foundations: Stakeholder Theory, which views enterprises as contractual networks of multiple stakeholders and argues fulfilling ESG responsibilities is key to balancing stakeholder demands and securing long-term resources, and Signaling Theory, which explains ESG practices reduce information asymmetry as credible signals to help enterprises gain trust, acquire resources, and boost performance. The literature review analyzes three areas: corporate performance evaluation methods (DuPont Analysis, BSC, EVA) with their advantages and limitations, new energy enterprise performance evaluation (noting positive impacts of R&D investment and government subsidies but over-reliance on traditional financial indicators), and ESG (tracing its origin, pointing out the lack of a unified global definition, and comparing international evaluation systems like MSCI and FTSE Russell with China’s fledgling localized systems that draw on international experience). Overall, the paper lays a theoretical and empirical groundwork for exploring the ESG-performance relationship (especially for China’s new energy enterprises) and identifies research gaps, such as the need for localized ESG systems and improved new energy enterprise performance evaluation frameworks.